1995
DOI: 10.1016/s0022-5347(01)67436-6
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Penile Color Flow Duplex Ultrasonography Using a Triple Drug Mixture

Abstract: Duplex ultrasonography is an accepted method to assess noninvasively arterial inflow to the penis. Optimal pharmacological agents as well as timing of the scan and stimulation during the scan continue to be debated. In an effort to achieve a more complete smooth muscle relaxation and capture what we perceived was a wide variation in interval to maximum arterial velocity, we revised our duplex protocol in January 1991. We report on 280 consecutive patients evaluated in this manner. Patients received 0.25 or 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…Our findings in the intracorporeal group are similar to the results reported by Govier et al 13 They found that peak systolic velocity was highest at 5 minutes, decreased at 15 minutes, and further declined by 30 minutes after intracorporeal injection of a triple-drug mixture. The reason for the results might be as follows.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings in the intracorporeal group are similar to the results reported by Govier et al 13 They found that peak systolic velocity was highest at 5 minutes, decreased at 15 minutes, and further declined by 30 minutes after intracorporeal injection of a triple-drug mixture. The reason for the results might be as follows.…”
Section: Discussionsupporting
confidence: 92%
“…[9][10][11][12] We judged that false-positive results would add to the patient's anxiety and could thus be counterproductive to the outcome of therapy. One must weigh the benefit of performing these tests for a patient with clear history of full rigid morning or night erections, or rigidity of 70% or more recorded at the base and tip of the penis, and sustained for more than 5 min on at least one erectile episode during Rigiscan monitoring of nocturnal penile rigidity, versus the risk of adding to the patient's anxiety with a false-positive result on penile vascular studies.…”
Section: Discussionmentioning
confidence: 99%
“…Functional classification of the male sexual cycle is the most physically quantifiable one;[13] therefore, we considered it as the basis of the current discussion.…”
Section: Discussionmentioning
confidence: 99%